2014
DOI: 10.1080/00222933.2014.946108
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the activity rhythm and population size of troglophilic mygalomorph spiders (Trechonasp., Dipluridae) in a quartzite cave in Minas Gerais, Brazil

Abstract: Records of mygalomorphs inhabiting caves have increased in the past years. We present data on a population of Trechona sp. spiders, found in a quartizite cave in Diamantina, Minas Gerais, Brazil. The spiders and their retreats were marked, and this population was followed for 17 months. The population consisted of up to 100 individuals, comprising the worlds' largest known cave-dwelling population of mygalomophs. The estimated population size (Jolly-Seber model) varied from 50.36 to 853.43, the latter consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The apparent absence of T. diamantina sp. nov. from epigean habitats and the additional cave records confirm the troglophile status attributed to this species by Guadanucci et al (2014). The small number of collected specimens compared to the observation of more than 100 specimens during our field study is also related to the troglophilic status of this species, as any impact on cave populations should be carefully weighted.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The apparent absence of T. diamantina sp. nov. from epigean habitats and the additional cave records confirm the troglophile status attributed to this species by Guadanucci et al (2014). The small number of collected specimens compared to the observation of more than 100 specimens during our field study is also related to the troglophilic status of this species, as any impact on cave populations should be carefully weighted.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to the previous records of Trechona diamantina sp. nov. in Guadanucci et al (2014), two caves (Lapa do Manéu and Lapa dos Pombos, all located in Diamantina) are here added to the geographical range. Despite our efforts to collect specimens at several epigean sites of the Diamantina Plateau, we only found these spiders inside caves, including aphotic zones far away from the entrances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the knowledge regarding subterranean fauna has been historically focused on limestone caves so that other kinds of rocks, such as siliciclastic, have received less attention (Sharratt et al 2000, Souza-Silva et al 2011. Despite quartzite caves being less frequent than caves in other lithologies, studies with fauna from these habitats have been conducted in some regions of the world, as in Cape Peninsula in South Africa (Sharratt et al 2000), in the Northwestern United States (Peck and Peck 1982), in the Amazon Tepuis in South America (Galán andHerrera 2006, Aubrecht et al 2012), in the Brazilian Atlantic Rain Forest (Zeppelini et al 2003, Gallão andBichuette 2015) and in Brazilian Savannah (Guadanucci et al 2015). Some of those studies have shown that quartzite and sandstone caves are important habitats for troglophilic and troglobitic fauna in Neotropics, thus deserving attention for conservation (Gallão andBichuette 2015, Souza-Silva et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gertsch 1982;Goloboff 1993;Hedin and Bond 2006), very few species were found in caves and usually represented in collections by few individuals or small populations (Trajano and Moreira 1991;Bernardi et al 2007), mainly at the cave entrance (Ribera 2004;Pedroso and Baptista 2014), and are considered, in general, as incidental cave dwellers (Trajano and Bichuette 2009). Nevertheless, Guadanucci et al (2014) recently reported a large cave-dwelling population, with more than 100 spiders of Trechona diamantina Guadanucci, Fonseca-Ferreira, Baptista & Pedroso, 2016 (family Dipluridae).…”
Section: Introductionmentioning
confidence: 99%